ANALISIS PENINGKATAN KAPASITAS SISTEM SELULER 4G LTE PADA SISTEM KOMUNIKASI HIGH ALTITUDE PLATFORM STATION - Waluyo, Catur Budi; Astuti, Yenni (Angkasa: Jurnal Ilmiah Bidang Teknologi, 2017)
In the development o f wireless communications, to provide high-speed data services and wide bandwidth become a challenge. One technique to make it happen is by using Multicarrier Orthogonal Frequency Division Multiplexing (OFDM) modulation, where in OFDM, frequency selective fading channel effect will be perceived flat fading by each subcarrier. One communication system that supports OFDM technology is Long Term Evolution (LTE) with various types of bandwidth configurations provided. To improve LTE performance in capacity building, coverage area and data rate, it can use multi antenna technique both in receiver and sender, and integrate with High altitude platform station (HAPs) system. In this study the estimation used is Linear Minimum Mean Square (LMMSE). The relationship o f the elevation angle and the K factor is directly proportional, but the elevation angle value is inversely proportional to the diameter o f the HAPs coverage area. In addition, the more the number o f used antennas, the greater the capacity served. Based on the simulation results, the system with estimation can be used to expand the coverage area to 215.77 km which is from 0.032 km in QPSK modulation, speed 60 kmpj with 2x2 antennas.